Evaluation of Lipid Profile in Psoriatic Patients Treated by Methotrexate And Retinoid - S. Ahmeid, Mutaz; A. Hamad, Noor; S. Najem, Wesam (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Psoriasis is a common disease with the population prevalence ranging from 2%to 3%. Its prevalence in the population is affected by genetic, environmental. Psoriasis isassociated with an atherogenic lipid profile but longitudinal changes in lipids around diseaseonset are unknown. Because of the wide range of comorbid conditions associated withpsoriasis, comprehensive screening and treatment must be implemented to most effectivelymanage psoriasis patients. The aim of this study is to examine the effect of type of treatment(methotrexate & retinoid) on serum lipid profiles for psoriatic patients. Methods: Comparedthe changes in lipid profiles in a psoriatic 50 patient , 20 of them as a control group never takea treatment, 15 psoriatic patient treated by methotrexate, and 15 psoriatic patient treated byretinoid. All lipid measures index data were abstracted. Random-effects models adjusting forage, sex and calendar year were used to examine trends in lipid profiles. Result: Decreaseserum total cholesterol, low density lipoprotein, and high density lipoprotein in psoriaticpatient on methotrexate, while increase triglyceride level with systemic retinoid. Conclusions:Psoriatic patients could be considered as a group with an increased atherosclerotic risk becauseof susceptibility in lipid profile.